SLOGAN OF “KULIAH SAK NGAJINE” IN PERSPECTIVE OF SPEECH ACT - Muyassaroh (English Language Teaching Journal, 2023)
This study aims at investigating speech act behind the slogan of "kuliah Sak Ngajine". Theory of speech act employed is the one belonged to Austin which consists of three kinds i.e. locution, illocution, and perlocution. Based on qualitative method used it is discovered that locutionary act of this slogan refers to having studying both common academic learning and Islamic courses. Illocution act of this slogan imply that Kuliah Sak Ngajine is having learning process followed by irfani values in order to make values of kepesantrenan emerge. Perlocutionionary act of Kuliah Sak Ngajine slogan indicates that not all the students implement learning process by irfani values properly. Keywords; slogan, speech act.